Reducing signal coupling and crosstalk in monolithic, mixed-signal integrated circuits - Clewell, Matthew John (Kansas State University, 2014)
Designers of mixed-signal systems must understand coupling mechanisms at the system, PC board, package and integrated circuit levels to control crosstalk, and thereby minimize degradation of system performance. This research examines coupling mechanisms in a RF-targeted high-resistivity partially-depleted Silicon-on-Insulator (SOI) IC process and applying similar coupling mitigation strategies from higher levels of design, proposes techniques to reduce coupling between sub-circuits on-chip. A series of test structures was fabricated with the goal of understanding and reducing the electric and magnetic field coupling at frequencies up to C-Band. Electric field coupling through the active-layer and substrate of the SOI wafer is compared for a variety of isolation methods including use of deep-trench surrounds, blocking channel-stopper implant, blocking metal-fill layers and using substrate contact guard-rings. Magnetic coupling is examined for on-chip inductors utilizing counter-winding techniques, using metal shields above noisy circuits, and through the relationship between separation and the coupling coefficient. Finally, coupling between bond pads employing the most effective electric field isolation strategies is examined. Lumped element circuit models are developed to show how different coupling mitigation strategies perform. Major conclusions relative to substrate coupling are 1) substrates with resistivity 1 kΩ·cm or greater act largely as a high-K insulators at sufficiently high frequency, 2) compared to capacitive coupling paths through the substrate, coupling through metal-fill has little effect and 3) the use of substrate contact guard-rings in multi-ground domain designs can result in significant coupling between domains if proper isolation strategies such as the use of deep-trench surrounds are not employed. The electric field coupling, in general, is strongly dependent on the impedance of the active-layer and frequency, with isolation exceeding 80 dB below 100 MHz and relatively high coupling values of 40 dB or more at upper S-band frequencies, depending on the geometries and mitigation strategy used. Magnetic coupling was found to be a strong function of circuit separation and the height of metal shields above the circuits. Finally, bond pads utilizing substrate contact guard-rings resulted in the highest degree of isolation and the lowest pad load capacitance of the methods tested.
Keywords: Coupling; Silicon-on-insulator; High-resistivity; Crosstalk; Thick-film; Mixed-signal; Electrical Engineering (0544); Electromagnetics (0607)